THE EFFECT OF USING CACO3 AND LIME GLASS IN THE PROBABILITY OF PORE STRUCTURE FORMING ON A CERAMIC GLASS BASED ON SCORIA BASALT ROCKS - Anton Sapto Handoko; David Candra Birawidha; Yusup Hendronursito; Kusno Isnugroho; Muhammad Amin; Sentausa Nuringjati; Syafriadi Syafriadi (Indonesian Mining Journal, 2022)
With the development of technology lately, the technology for making lightweight materials is also growing, where the goal is to reduce the total weight of the material without reducing its mechanical strength. Several parameters that influence the manufacture of lightweight materials are the number of pores, materials weight, and physical resistance. One commonly used method is mixing ceramic glass with a foaming agent. In this study, basalt rock from East Lampung, Indonesia, and lime glass was used as a ceramic glass material mixed with CaCO3, which melted down at a temperature of 1200 0C. Variations in composition were carried out by mass comparison between basalt and lime glass, namely A sample (100:0), B sample (70:30), C sample (50:50), and D sample (30:70) with 50%wt CaCO3 added for each sample and heated up to 1200 0C. Treatment variations (annealed and normalized) are also applied to see the phenomena occur. Based on the characterization results, the best sample obtained is in B sample with normalized treatment, whose has porosity value of 53.2% and density value of 1.08 gr/cm3. Based on the results of the SEM test, the pores with a size ≤ 0.5µm are 95%, and ≥ 0.5µm are 5%, where the crystals formed are pyroxene and calcite with the compositions of CaO and SiO2, respectively 39.46% and 41.90%.